Hydrogen BECCS Innovation Programme Phase 1 : BIG-H2 Phase 1 Final Report : H2 production via Biomass gasification Integrated with innovative one step Gas shift reforming and separation (BIG-H2): BIG-H2 Phase 1 Final Report : H2 production via Biomass gasification Integrated with innovative one step Gas shift reforming and separation (BIG-H2). (2022) - Unknown
No abstract available